STMIK Primakara Academic Data Audit Based on DAF (Data Audit Framework) - Ananta Wijaya; Adisimakrisna Peling; Ida Bagus Alit Swamardika (International Journal of Engineering and Emerging Technology, 2016)
This time the development of a large amount of data occurs in various sectors, one of them is education sector. Although addition of data occurs every day, college does not yet have a formal strategy to perform collection, observation, and maintenance of the data. This condition is experienced by STMIK Primakara. The audit framework is required to mapping the existing data in higher education. Joint Information Systems Committee (JISC) develop Data Audit Framework that contains the stages of structured work to audit the academic data. The implementation of DAF on the academic data STMIK Primakara produce SWOT analysis which represent data asset condition.